Greenness Availability and Respiratory Health in a Population of Urbanised Children in North-Western Italy - Squillacioti, Giulia; Bellisario, Valeria; Levra, Stefano; Piccioni, Pavilio; Bono, Roberto (International journal of environmental research and public health, 2019)
Paediatric Asthma contributes in paediatric global burden of diseases, as the most common chronic disease in children. Children are exposed to many environmental risk-factors, able to determine or worsen respiratory diseases, and contributing to asthma and asthma-like symptoms increases, especially in metropolitan areas. In urban settings, surrounding vegetation (greenness) may provide important benefits to health, including the promotion of physical activity and the mitigation of air and noise pollution. The aim of this study was to investigate the association between greenness and respiratory health. A total of 187 children (10–13 yrs old) were recruited in Turin, the north-western part of Italy. The prevalence of asthma and asthma-like symptoms was calculated from self-reported data collected by SIDRIA questionnaire. Spirometry test was performed to obtain respiratory flow measurements. Greenness was measured at individual level through the Normalised Difference Vegetation Index (NDVI) estimations from remote-sensing images. Higher exposure (3rd tertile vs. 1st tertile) to NDVI was associated to significantly lower ORs for asthma [0.13 CI 95% 0.02–0.7, p = 0.019], bronchitis [0.14 CI 95% 0.05–0.45, p = 0.001], and current wheezing [0.25 CI 95% 0.09–0.70, p = 0.008]. A significative positive association was found between greenness and FEF25–75, since children exposed to the 2nd tertile of NDVI reported a significantly decreased FEF25–75 compared to those in the 3rd tertile [B: −2.40; C.I.95%: −0.48–0.01; p = 0.049]. This cross-sectional study provided additional data on still inconsistent literature referring to respiratory health in children and green spaces, attesting a positive effect of greenness in a specific area of Italy. Further research is still needed.